Promoting productivity and market access technologies and approaches to improve farm income and livelihoods in Ethiopia: Lessons from action research projects - Mekonnen, Kindu; Yasabu, Simret; Gebremedhin, Berhanu; Woldemeskel, Endalkachew; Tegegne, Azage; Thorne, Peter J. (International Livestock Research Institute, 2019)
On 8–9 December 2016, ILRI held a workshop and exhibition in Addis Ababa for researchers to share their experiences in implementing action research projects. Action research projects superimpose research protocols on development interventions along commodity value chains and systems to assess their feasibility, effectiveness and outcomes. In the years prior to 2016, ILRI implemented several action research projects in target countries of Africa, including Kenya and Ethiopia. The objectives of the workshop and exhibition were: 1. To create wider awareness and knowledge about the technologies and approaches that are tested and validated by LIVES, Africa RISING, ILRI Accelerated Value Chain Development (AVCD) and N2Africa; 2. To facilitate the uptake of successful experiences/innovations that combine productivity enhancement and market access; 3. To facilitate dialogue on improving the linkage/partnership between research and development actors and facilitate cross learning. The expected outcomes of the workshop and exhibition were: 1. Improved awareness about the technical, organizational and institutional interventions tested and validated by the projects; 2. Improved understanding of the role and utility of action research approaches, opportunities and constraints; 3. Enhanced probability of scaling out and up of the tested technologies and approaches to achieve sustainable and market-oriented smallholder agricultural development. A compilation of papers presented at the ‘Promoting productivity and market access technologies and approaches to improve farm income and livelihoods in Ethiopia: Lessons from action research projects’ workshop and exhibition are included below.